1994
DOI: 10.1121/1.410277
|View full text |Cite
|
Sign up to set email alerts
|

The multidimensional nature of pathologic vocal quality

Abstract: Although the terms "breathy" and "rough" are frequently applied to pathological voices, widely accepted definitions are not available and the relationship between these qualities is not understood. To investigate these matters, expert listeners judged the dissimilarity of pathological voices with respect to breathiness and roughness. A second group of listeners rated the voices on unidimensional scales for the same qualities. Multidimensional scaling analyses suggested that breathiness and roughness are relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(62 citation statements)
references
References 25 publications
3
58
1
Order By: Relevance
“…Data were drawn from four previously published studies ͑Kreiman et al., 1993;Kreiman et al, 1994;Rabinov et al, 1995;Kreiman and Gerratt, 1996͒ and one unpublished study ͑Chhetri, 1997͒. Two of these studies ͑Kreiman et al., 1993;Rabinov et al, 1995͒ were specifically concerned with issues of rating reliability.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data were drawn from four previously published studies ͑Kreiman et al., 1993;Kreiman et al, 1994;Rabinov et al, 1995;Kreiman and Gerratt, 1996͒ and one unpublished study ͑Chhetri, 1997͒. Two of these studies ͑Kreiman et al., 1993;Rabinov et al, 1995͒ were specifically concerned with issues of rating reliability.…”
Section: Methodsmentioning
confidence: 99%
“…Two groups of raters participated in the studies reported in Kreiman et al ͑1994͒. The first group judged the similarity of pairs of voices with respect to breathiness or roughness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…͑Hillen-brand, 1988, also commented that his stimuli sounded somewhat unnatural.͒ Further, previous studies assessing the role of noise and perturbation in determining voice quality have always assessed quality in terms of specific scales like breathiness, roughness, or hoarseness. However, the reliability of such scales has been repeatedly questioned, and their validity as measures of quality is also questionable ͑e.g., Jensen, 1965;Kreiman, Gerratt, and Berke 1994;see Kreiman et al, 2005, for review͒. A final limitation of previous synthesis studies is the fact that jitter, shimmer, and noise have been manipulated independently of one another, and the perceptual interactions among these three variables have not been investigated. Acoustically, these attributes are obviously related.…”
Section: Introductionmentioning
confidence: 99%
“…Since many researchers regard "breathiness" as being caused by glottal air leakage [1,4], acoustic measures of breathiness may serve as a pool supplying useful candidates in the assessment of glottal closure. The "breathiness measure" most commonly encountered is the already mentioned H1H2 [3,[9][10][11]13]. Additionally, de Krom determined the harmonics to noise ratio (HNR) and several measures of the spectral slope as -somewhat ambiguous -best correlates of breathiness in a thorough study on the relation between acoustic measures and perceptual voice attributes [3].…”
Section: Introductionmentioning
confidence: 99%